2019
DOI: 10.1186/s12885-019-5804-0
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of receptor tyrosine kinase inhibitors and cancer metabolism: implications for treatment and discovery of potential therapeutic signatures

Abstract: Background Receptor tyrosine kinase (RTK) inhibitors are frequently used to treat cancers and the results have been mixed, some of these small molecule drugs are highly successful while others show a more modest response. A high number of studies have been conducted to investigate the signaling mechanisms and corresponding therapeutic influence of RTK inhibitors in order to explore the therapeutic potential of RTK inhibitors. However, most of these studies neglected the potential metabolic impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
4
0
1
Order By: Relevance
“…Obtained results showed an elevation in serum urea level in erlotinib group suggesting a metabolic impact of erlotinib as a tyrosine kinase inhibitor on liver cells. Previous studies on cancer cell lines showed an effect of tyrosine kinase inhibitors on N-acetylglutamate synthase a key enzyme in the urea cycle 26 , 27 . We also postulate that erlotinib may interfere with glutamate incorporation in ERK1/2 stimulatory signals through halting glutamate receptors activation by Src tyrosine kinases 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Obtained results showed an elevation in serum urea level in erlotinib group suggesting a metabolic impact of erlotinib as a tyrosine kinase inhibitor on liver cells. Previous studies on cancer cell lines showed an effect of tyrosine kinase inhibitors on N-acetylglutamate synthase a key enzyme in the urea cycle 26 , 27 . We also postulate that erlotinib may interfere with glutamate incorporation in ERK1/2 stimulatory signals through halting glutamate receptors activation by Src tyrosine kinases 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies evaluated tyrosine kinase inhibitors effect on N-acetyl glutamate synthase, which is a urea cycle key enzyme (Li, J. et al, 2019) (Pham-Danis C. et al, 2019. The current study showed that pemetrexed might interfere with glutamate incorporation in ERK1/2 stimulatory signals by halting glutamate receptors activation by Src tyrosine kinases, which may direct glutamate towards the elevation of urea formation in the blood.…”
Section: Discussionmentioning
confidence: 73%
“…Tyrosine kinase inhibitors have an impact on the urea cycle enzyme N-acetylglutamate synthase (Li, 2019). By inhibiting glutamate receptors, erlotinib may prevent glutamate from reacting with ERK1/2 stimulatory signals.…”
Section: Discussionmentioning
confidence: 99%